Impact of an accelerated measles-mumps-rubella (MMR) vaccine schedule on vaccine coverage: An ecological study among London children, 2012–2018. Issue 3 (24th January 2022) - Lacy, Joanne; Tessier, Elise; Andrews, Nick; White, Joanne; Ramsay, Mary; Edelstein, Michael
Abstract: Background: Vaccination coverage of dose two of MMR (MMR2) at 5th birthday has been consistently low in London and measured 76.3% in 2018/19. Since the early 2000s seven boroughs in London started offering dose two earlier, from 15 to 18 months onwards instead of the recommended 3 years 4 months. In this study we investigate whether the accelerated schedule of MMR2 leads to a change in coverage of MMR2 and other childhood vaccines with an ecological study using childhood immunisation data from 2009 to 2018 in London. Methods: We modelled coverage used generalized estimating equations (GEE) adjusted for year and DTaP/IPV/Hib3 coverage measured at 2nd birthday as a proxy for baseline local vaccination programme performance to determine the percentage point difference in coverage of MMR2 and other childhood vaccines. Results: Average MMR2 coverage was higher among early implementing boroughs from 2012/13 onwards. Coverage difference was highest in 2017/18 (9.2 percentage points, 95% CI 4.8, 13.5, p < 0.001). On average over the 6 years, compared to London boroughs on the routine schedule, MMR2 coverage among early implementing boroughs was 3.3 percentage points higher (95% CI 1.3, 5.3, p = 0.01) after adjusting for DTaP/IPV/Hib3 coverage, IMD score and year. Conclusion: Earlier vaccination of MMR2 is associated with significantly higher coverage at five years for this vaccine in London. Further research is needed to assess the association at a more granular level, but our findings underline a potential opportunity to increase MMR coverage.